Dampak COVID-19 Terhadap Kaum Perempuan: Perspektif Feminisme - Kirana Mahdiah Sulaeman; Fenny Rizka Salsabila (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2020)
This article discusses the social impact of the COVID-19 pandemic on women globally. Various health protocols have been implemented by more than 100 countries since March 2020 to deal with COVID-19, especially lockdown and work from home (WFH) regulations. These protocols have caused various effects, include the downfall of the world economy. This article seeks to answer the question of how the impact of WFH and economic downfall on women. This question arises because women have already faced inequality and vulnerability even before COVID-19. To answer this question, the author will use data from mass media, journal articles, and various official documents. the author uses the perspective of feminism in International Relations to analyze the issue. This study finds that the impact of the COVID-19 pandemic is not gender-neutral. However, it is hitting women even harder with three main impacts, first, is the double burden of childcare and work. Second, is the threat toward the possibility of domestic violence (KDRT), and the third is the inequality treatment in the economic sector. Artikel ini membahas dampak sosial pandemi COVID-19 secara global terhadap kaum perempuan. Berbagai protokol kesehatan telah diberlakukan oleh lebih dari 100 negara sejak Maret 2020 untuk menangani COVID-19, terutama aturan lockdown dan work from home (WFH). Hal ini telah menimbulkan berbagai dampak sampingan, terutama, memburuknya kondisi perekonomian dunia. Pertanyaan penelitian yang berusaha dijawab dalam artikel ini adalah bagaimana dampak kebijakan WFH yang disertai kesulitan ekonomi terhadap perempuan? Pertanyaan ini muncul karena sebelum COVID-19, sebagian kaum perempuan telah berada dalam kondisi ketidaksetaraan dan kerentanan. Untuk menjawab pertanyaan ini, penulis akan menggunakan data-data dari media massa, artikel jurnal, dan berbagai dokumen resmi. Penulis menggunakan perspektif feminisme dalam Hubungan Internasional untuk menganalisis isu ini. Temuan dari penelitian ini adalah bahwa imbas pandemi COVID-19 sesungguhnya tidaklah netral bagi semua gender, namun memukul perempuan lebih keras dengan adanya tiga dampak utama, yaitu pertama, beban ganda dalam pengasuhan anak dan pekerjaan. Kedua, yaituancaman terhadap kemungkinan terjadinya tindakan Kekerasan Dalam Rumah Tangga (KDRT), serta yang ketiga, yaitu ketidaksetaraan perlakuan dalam sektor ekonomi. This article discusses the social impact of the COVID-19 pandemic on women globally. Various health protocols have been implemented by more than 100 contries since March 2020 all countries in the world to deal with COVID-19, especially lockdown and work from home (WFH) regulations. These protocols have caused various side effects, one of which isinclude the downfall of the world economy. This article seeks to answer the question of how the impact of WFH and economic downfall on women. This question arises because, women have already faced inequality and vulnerability even before COVID-19, some women were already experiencing inequality and vulnerability. To answer this question, the author will use data from the mass media, journal articles, and various official documents. To analyze, the author uses the perspective of feminism in International Relations to analyze the issue. This study finds that the impact of the COVID-19 pandemic is not gender-neutral. However, it is hitting women even harder with three main impacts, first, is namely the double burden of childcare and work.Second, is, the threat of toward the possibility of dDomestic vViolence (KDRT), and the third is the inequality of treatment in the economic sector.